Miracle cures saints, pilgrimage, and the healing powers of belief - Scott, Robert A., 1935- (Berkeley, Calif. : University of California Press, 2010)
In this work, Scott explores the realities of religious healing. He inquires into the power of relics, apparitions, and the transformative nature of sacred journeying and shines new light on the roles belief, hope, and emotion can play in healing.
Prologue -- Appealing to saints for miracles -- Life in the Middle Ages -- Saints -- Apparitions -- Pilgrimage and shrines -- Saints and healing -- Disease -- The role stress in illness -- Belief, hope, and healing -- Framing, confessing, and healing -- Appendix A: Accounts of miracles at medieval shrines.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Spiritual healing; Healing -- Religious aspects -- Christianity; Miracles; RELIGION / Christian Theology / General; Electronic books